Initial Use of a Flexible Open Learner Model (International Conference on Computers in Education, 2013)
This paper give s an overview of the Next -TELL open learner model and initial levels of student use of this competency -based open learner model. It is sufficiently flexible to allow use in different ways, taking data from a range of sources. Levels of use suggest that the approach would be taken up by students, if adopted by their teachers.